Transcatether closure of an atrial redirection baffle leak - Soriano Brian; Stout Karen; Cailes Colleen; Jones Thomas (Wolters Kluwer Medknow Publications, 2009)
We present the case of a woman born with transposition of the great arteries, who was surgically repaired with the Mustard technique. Because of interatrial shunting, she was brought to the cardiac catheterization laboratory for device closure. Matrix-array 3D transesophageal echocardiography enabled visualization of both baffle leaks and demonstrated its orientation in a fashion superior to 2D imaging, had it been used alone. The leaks were successfully closed with a single transcatheter device.